Praktik Peliyanan dan Pendisiplinan Tubuh Lewat Bahasa Kekerasan di Percakapan Twitter - Zul’azmi, Helmi Naufal (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
This article aimed to identify how violent languages are operated for othering and disciplining the body as an exercise of power over the LGBTIQ groups in Indonesia. The analyzed violent language was taken from a conversation on Twitter that responds to Deddy Corbuzier’s podcast video with the title “TUTORIAL JADI G4Y DI INDO!!= PINDAH KE JERMAN (tonton sblm ngamuk) RAGIL AND FRED”. The issues of violence in language have been arising when the words used by Twitter accounts @cholilnafis, @anasabuabdillah, @mas_po_sanusi, @ridwan2474, @djoesa, @defrizonz, and @samsularifin000 are seen in a particular way in the context of their response to Deddy’s podcast video. This article shows that there is a process of othering and disciplining the body through the choices of words that contain elements of violence. Violent languages are operated to alienate others, as in the concept of “blaming others”. From Lozano and Laurent’s perspective, “blaming others” is accusing minorities under social inappropriateness instead of seeing their own fault. Meanwhile, the process of disciplining the body moves through violent languages that are associated with interpretation of Islamic discourse.